Effective Ca2+-doping in Sr1-xCaxFeO3-δ oxygen carriers for chemical looping air separation: A theoretical and experimental investigation. (1st January 2021) - Jia, Ting; Popczun, Eric J.; Lekse, Jonathan W.; Duan, Yuhua
Graphical abstract: Highlights: The vacancy formation energy reduces first and then increases with Ca 2+ increasing. The electrostatic interaction dominates the effect of Ca 2+ doping. The oxygen migration barrier is lowered upon Ca 2+ doping. An appropriate Ca 2+ doping (0.125–0.375) promotes the oxygen ion diffusion. A material design clue for designing high reactivity oxygen carriers is proposed. Abstract: Perovskite iron oxides are promising oxygen carrying materials due to their effectiveness and the low cost of iron. The effect of Ca 2+ doping on oxygen ion diffusion in Sr1-x Cax FeO3-δ (x = 0, 0.125, 0.25, 0.375, 0.5) is investigated by combining density functional theory (DFT) calculations and experimental measurements. The oxygen ion diffusion is determined by two key factors of oxygen vacancy formation and migration. The DFT results show that the oxygen vacancy formation energies greatly decrease as Ca 2+ content reaches x = 0.125, then gradually decrease with Ca 2+ contents up to 0.375, and finally increase as the Ca content reaches x = 0.5. A combination of experimental thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) results corroborate this trend for Ca 2+ contents between 0 and 0.4. The Fe-O bonding dominates the effect of Ca 2+ doping on the oxygen vacancy formation. Shortened Fe-O bonds cause the decrease in the formation energy at lower Ca 2+ contents, while the lengthened bonds by FeO6 octahedron distortion cause the increase in the formation energy at higher Ca 2+ contents. Kinetically, the oxygen migration barrier is lowered upon Ca 2+ doping through the increasing lattice spacing for oxygen diffusion. Therefore, an appropriate Ca 2+ doping of x = 0.125–0.375 promotes the oxygen ion diffusion in Sr1-x Cax FeO3-δ . Our findings provide the effective Ca 2+ doping value for Sr1-x Cax FeO3-δ and a material design clue for the isovalent A-site doping system of oxygen carriers.